Human oocyte meiotic maturation is associated with a specific profile of alternatively spliced transcript isoforms. Issue 9 (9th August 2021) - Cornet‐Bartolomé, David; Barragán, Montserrat; Zambelli, Filippo; Ferrer‐Vaquer, Anna; Tiscornia, Gustavo; Balcells, Susanna; Rodriguez, Amelia; Grinberg, Daniel; Vassena, Rita
Abstract: The transition from a transcriptionally active state (GV) to a transcriptionally inactive state (mature MII oocytes) is required for the acquisition of oocyte developmental competence. We hypothesize that the expression of specific genes at the in vivo matured (MII) stage could be modulated by posttranscriptional mechanisms, particularly regulation of alternative splicing (AS). In this study, we examined the transcriptional activity of GV oocytes after ovarian stimulation followed by oocyte pick‐up and the landscape of alternatively spliced isoforms in human MII oocytes. Individual oocytes were processed and analyzed for transcriptional activity (GV), gene expression (GV and MII), and AS signatures (GV and MII) on HTA 2.0 microarrays. Samples were grouped according to maturation stage, and then subgrouped according to women's age and antral follicular count (AFC); array results were validated by quantitative polymerase chain reaction. Differentially expressed genes between GV and MII oocytes clustered mainly in biological processes related to mitochondrial metabolism. Interestingly, 16 genes that were related to the regulation of transcription and mitochondrial translation showed differences in alternatively spliced isoform profiles despite not being differentially expressed between groups. Altogether, our results contribute to our understanding of the role of AS in oocyte developmental competence acquisition.